The Combination of TIM3-Based Checkpoint Blockade and Oncolytic Virotherapy Regresses Established Solid Tumors. Issue 1 (1st January 2023) - Gowan, Cody C.; Bartee, Mee Y.; Flores, Erica; Aksoy, Bulent A.; Templeton, Conor; Baillie, Kati; Happe, Myroslawa; Bartee, Eric
Abstract : T-cell immunoglobulin and mucin domain 3 (TIM3) is emerging as a potential target for antibody-based checkpoint blockade. However, the efficacy of TIM3 blockade in combination with other treatment modalities, has not been extensively studied. In the current work we combined TIM3 blockade with myxoma virus-based oncolytic virotherapy (OV). Our results demonstrate that myxoma virus's ability to initiate an immense antitumor immune response complements the ability of TIM3 blockade to shift the tumor microenvironment to a more proinflammatory state. As a result, the combination of TIM3 blockade and OV is able to completely eradicate established disease, while neither monotherapy is effective. These data represent the first demonstration that OV can enhance the efficacy of TIM3 blockade and suggest that this treatment may need to be incorporated into more aggressive, combinatorial regimens in order to fulfill its potential as an immunotherapeutic.